Penyuluhan mengenai Akurasi Pelafalan Kata dalam Bahasa Inggris melalui Utilisasi International Phonetic Alphabet di Universitas Muhammadiyah Ahmad Dahlan Palembang - Moehamad Ridhwan; Tiur Simanjuntak; Evi Agustinasari; Risnawati Risnawati; Sunani Sunani (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2026)
This Community Service activity aims to introduce the English pronunciation method through the use of phonetic sound symbols known as the International Phonetic Alphabet (IPA). The target of the activity was students of the Medical Laboratory Technology Study Program, University of Muhammadiyah Ahmad Dahlan. The main focus of the activity was to convey that the differences between spelling and pronunciation in English can be bridged with a consistent mastery of phonetic symbols. The methods used include counseling on sound variations in English words as well as short training with pronunciation drilling techniques on words that have foreign sounds for Indonesian speakers. This activity is designed to improve participants' phonological awareness and pronunciation skills in a practical and fun way. The results of the evaluation showed that participants gave very positive responses, assessing this activity as a rewarding and engaging experience. This activity is expected to be an educational model in strengthening English phonetic competence, especially for non-language students. In the future, this phonetic approach can be further developed in profession-based foreign language learning curricula to improve the accuracy of cross-cultural and professional communication.